Decontamination efficacy of erbium:yttrium–aluminium–garnet and diode laser light on oral Candida albicans isolates of a 5-day in vitro biofilm model - Sennhenn-Kirchner, Sabine (Lasers Med Sci, 2008)
The different forms of superficial and systemic candidiasis are often associated with biofilm formation on surfaces of host tissues or medical devices. The biofilm formation of Candida spp., in general, necessitates significantly increased amounts of antifungal agents for therapy. Often the therapeutic effect is doubtful. A 5-day biofilm model with oral Candida isolates was established according to Chandra et al. [39](J Dent Res 80:903–908, 2001) on glass and titanium surfaces and was modified by Sennhenn-Kirchner et al. [40](Z Zahnärztl Implantol 3:45–51, 2007) to investigate different aspects unanswered in the field of dentistry. In this model, the efficacy of erbium:yttrium–aluminium–garnet (Er:YAG) light (2940 nm, 100 mJ, 10 Hz, 300 μs pulsed mode applied for 80 s) and diode laser light (810 nm, 1 W, continuous wave mode applied for 20 s with four repetitions after 30 s pauses each) was evaluated and compared to untreated controls. The photometric evaluation of the samples was completed by observations on morphological changes of yeast cells grown in the biofilm. Compared to the untreated controls Candida cells grown in mature in vitro biofilms were significantly reduced by both wavelengths investigated. Comparison between the different methods of laser treatment additionally revealed a significantly greater effect of the Er:YAG over the diode laser. Scanning electron microscopy findings proved that the diode laser light was effective in direct contact mode. In contrast, in the areas without direct contact, the fungal cells were left almost unchanged. The Er:YAG laser damaged the fungal cells to a great extent wherever it was applied.